STUDENTS’ PERCEPTION OF PEER MENTORING AND MATHEMATICS ANXIETY AMONG SENIOR SECONDARY SCHOOL STUDENTS IN NIGERIA - Malik, Nasrudeen Ayinde; Fakokunde, Jubril Busuyi; Iroko, Ganiyu Adisa; Adams, Hassanat Taiwo (Indonesian Journal of Elementary Teachers Education, 2024)
This study examined students’ perceptions of peer mentoring and mathematics anxiety among senior secondary school students in Nigeria. The study explores students' attitudes toward participating in peer mentoring programmes. Descriptive statistical techniques were used to answer the research questions. The findings of this study revealed that a significant proportion of students strongly agreed that the mentoring programme was transformative and provided unique learning opportunities for academic performance. It was further revealed that the mentoring programme had a remarkable effect on reducing mathematics anxiety. Therefore, it was recommended that the Nigerian government should encourage the expansion and continuity of peer mentoring programmes in schools. It also suggested that there should be training and ongoing professional development for mentors.